Assessment of the Levels of Potentially Toxic Elements Contained in Natural Bentonites Collected from Quarries in Turkey - Altıkulaç, Aydan; Turhan, Şeref (American Chemical Society (ACS), 2023)
Potentially toxic elements (PTEs) are an important type of pollutant, causing constant and far-reaching concerns around the world due to their increase in the mining process. Bentonite formed by the alteration of glass-rich volcanic rocks is a smectite clay consisting mostly of montmorillonite. Bentonite is an important mineral used in a wide range of applications in many fields such as oil and gas, agriculture, food, pharmacological, cosmetic, and construction industries due to its unique qualities. Given the widespread distribution of bentonite in nature and its use in a wide variety of consumer products, it is inevitable that the general population will be exposed to PTEs contained in bentonites. In this study, concentrations of PTEs in 69 bentonite samples collected from quarries located in different geographical regions of Turkey were analyzed by an energy-dispersive X-ray fluorescence spectrometric method. The average concentrations of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Zr, and Pb in bentonite samples were found to be 3510, 95, 129, 741, 30,569, 67, 168, 25, 62, 9, 173, and 28 mg/kg dry weight, respectively. Results of the enrichment factor relating to Earth's crust average indicated moderate enrichment with Cr, Ni, and Pb and significant enrichment with Co and As.
Keywords: Chemistry; Ttoxic elements; QD1-999; 13. Climate action